How has implementation been incorporated in health technology assessments in the United Kingdom? A systematic rapid review - Robert Heggie; Kathleen Boyd; Olivia Wu (BMC, 2021)
Abstract Objectives Health interventions in a clinical setting may be complex. This is particularly true of clinical interventions which require systems reorganization or behavioural change, and/or when implementation involves additional challenges not captured within a clinical trial setting. Medical Research Council guidance on complex interventions highlights the need to consider economic evaluation alongside implementation. However, the extent to which this guidance has been adhered to, and how, is unclear. The failure to incorporate implementation within the evaluation of an intervention may hinder the translation of research findings into routine practice. This will have consequences for patient care. This study examined the methods used to address implementation within health research conducted through funding from the National Institute for Health Research (NIHR) Health Technology Assessment (HTA) programme. Methods We conducted a rapid review using a systematic approach. We included all NIHR HTA monographs which contained the word "implementation" within the title or abstract published between 2014 and 2020. We assessed the studies according to existing recommendations for specifying and reporting implementation approaches in research. Additional themes which were not included in the recommendation, but were of particular relevance to our research question, were also identified and summarized in a narrative synthesis. Results The extent to which implementation was formally incorporated, and defined, varied among studies. Methods for examining implementation ranged from single stakeholder engagement events to the more comprehensive process evaluation. There was no obvious pattern as to whether approaches to implementation had evolved over recent years. Approximately 50% (22/42) of studies included an economic evaluation. Of these, two studies included the use of qualitative data obtained within the study to quantitatively inform aspects relating to implementation and economic evaluation in their study. Discussion A variety of approaches were identified for incorporating implementation within an HTA. However, they did not go far enough in terms of incorporating implementation into the actual design and evaluation. To ensure the implementation of clinically effective and cost-effective interventions, we propose that further guidance on how to incorporate implementation within complex interventions is required. Incorporating implementation into economic evaluation provides a step in this direction.